(3cJGH GdJLGQHs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s ((3Ydi Hf CjhH Hf jhSa Gdbhfhi Gdehdhi s)
(3ChdgG (B:s
(3LYd ef JLGQH GdQGRi CedGgG (B[(3Ydi (B] (3HYV JdGejPI hCfG QJHJgG JQjJHkG NGUkG HMSH GdCYVGA s
(3BNQgG (B:s
(3EgdjL CUaQ , YTQjf OQgekG , jWjN EdGgdjdL hMOg , hjTQHI gPG BNQ GdcJGH s
(3eLQHGJs
(3LeYgG CMO JdGejPIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdChd (B- (3U (B39 s
Keywords: (3GdWHs